1995
DOI: 10.1002/syn.890200210
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective sigma ligands interfere with the glutamate‐activated NOS pathway in hippocampal cell culture

Abstract: We studied neuroprotective properties of 12 structurally different sigma site ligands in primary rat hippocampal cell cultures and analyzed whether they interfere with glutamate-induced activation of the nitric oxide synthase (NOS) pathway. Neurotoxicity was triggered with 1 mM glutamate on day 8 of culture. Cells were treated with various concentrations of the compounds for 7 days before glutamate exposure (prolonged pretreatment), or during glutamate exposure (acute treatment). Protection was seen after prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Over the years, a number of studies have reported that DM has neuroprotective effects (Choi 1987;Steinberg et al, 1988;George et al, 1988;Prince and Feeser, 1988;Monyer and Choi, 1988;DeCoster et al, 1995;Lesage et al, 1995;Berman and Murray, 1996;Britton et al, 1997;Haberecht et al, 1997). The mechanism of action responsible for this neuroprotective activity has been attributed to DM's potential antagonistic effect on the NMDA receptor complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, a number of studies have reported that DM has neuroprotective effects (Choi 1987;Steinberg et al, 1988;George et al, 1988;Prince and Feeser, 1988;Monyer and Choi, 1988;DeCoster et al, 1995;Lesage et al, 1995;Berman and Murray, 1996;Britton et al, 1997;Haberecht et al, 1997). The mechanism of action responsible for this neuroprotective activity has been attributed to DM's potential antagonistic effect on the NMDA receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies using animal models of cerebral ischemia and hypoglycemic neural injuries have demonstrated that DM possesses neuroprotective activity Monyer and Choi, 1988;Prince and Feeser, 1988;Steinberg et al, 1988;Britton et al, 1997;Tortella et al, 1999). Attempts to attribute the neuroprotective activity of DM to antagonism of glutamate receptors have been complicated by conflicting reports about its ability to prevent glutamate excitatory toxicity (Choi, 1987;DeCoster et al, 1995;Lesage et al, 1995;Berman and Murray, 1996;Haberecht et al, 1997). Nevertheless, the effect of DM on the degeneration of dopaminergic neurons has not been studied.…”
mentioning
confidence: 99%
“…Disfinct sensitivity of a sites to antagonists Behavioural, neurochemical and electrophysiological studies led to the discovery of the neuromodulatory effects of a receptor ligands on NMDA(N-methyl-D-aspartate)-operated glutamatergic neurotransmission, effects which would account for the neuroprotective actions, amnesic and cognitive effects of a drugs (Monnet et al, 1990;1992a;Pontecorvo et al, 1991;Martin et al, 1992;Maurice et al, 1994a, b;DeCoster et al, 1995;Lesage et al, 1995;Lockhart et al, 1995). In an in vivo extracellular electrophysiological paradigm, a ligands that enhance the neuronal response to NMDA were defined as a agonists [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…15 In vitro, -receptor ligands prevent glutamate-induced activation of nitric oxide synthase (NOS). 16 Nitric oxide (NO) is an important mediator in ischemic brain injury. [17][18][19] Specifically, NO derived from constitutively expressed NOS in neurons (nNOS) and the inducible isoform expressed by many cells (iNOS) are important in excitotoxic injury cascades.…”
mentioning
confidence: 99%